Modulating effects of FGF12 variants on NaV1.2 and NaV1.6 being associated with developmental and epileptic encephalopathy and Autism spectrum disorder: a case series - Seiffert, Simone; Pendziwiat, Manuela; Bierhals, Tatjana; Goel, Himanshu; Schwarz, Niklas; Ven, Amelie van der; Boßelmann, Christian Malte; Lemke, Johannes; Syrbe, Steffen; Willemsen, Marjolein Hanna; Hedrich, Ulrike B. S.; Helbig, Ingo; et al. (EBioMedicine, 2022)
Objective - Fibroblast Growth Factor 12 (FGF12) may represent an important modulator of neuronal network activity and has been associated with developmental and epileptic encephalopathy (DEE). We sought to identify the underlying pathomechanism of FGF12-related disorders. - Methods - Patients with pathogenic variants in FGF12 were identified through published case reports, GeneMatcher and whole exome sequencing of own case collections. The functional consequences of two missense and two copy number variants (CNVs) were studied by co-expression of wildtype and mutant FGF12 in neuronal-like cells (ND7/23) with the sodium channels NaV1.2 or NaV1.6, including their beta-1 and beta-2 sodium channel subunits (SCN1B and SCN2B). - Results - Four variants in FGF12 were identified for functional analysis: one novel FGF12 variant in a patient with autism spectrum disorder and three variants from previously published patients affected by DEE. We demonstrate the differential regulating effects of wildtype and mutant FGF12 on NaV1.2 and NaV1.6 channels. Here, FGF12 variants lead to a complex kinetic influence on NaV1.2 and NaV1.6, including loss- as well as gain-of function changes in fast and slow inactivation. - Interpretation - We could demonstrate the detailed regulating effect of FGF12 on NaV1.2 and NaV1.6 and confirmed the complex effect of FGF12 on neuronal network activity. Our findings expand the phenotypic spectrum related to FGF12 variants and elucidate the underlying pathomechanism. Specific variants in FGF12-associated disorders may be amenable to precision treatment with sodium channel blockers. - Funding - DFG, BMBF, Hartwell Foundation, National Institute for Neurological Disorders and Stroke, IDDRC, ENGIN, NIH, ITMAT, ILAE, RES and GRIN